PENGGUNAAN MEDIA WORDWALL UNTUK MENINGKATKAN KETERLIBATAN SISWA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Nada Nadhifa Putri; Agus Fakhruddin; Mokh Iman Firmansyah (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This research is motivated by the low interest of students in learning Islamic Religious Education (PAI), which often becomes a challenge for educators. One of the efforts to address this issue is by adaptively utilizing interactive learning media, such as Wordwall. The aim of this study is to understand the extent to which the use of Wordwall can increase student engagement in Islamic education learning. Using an action research design methodology, this study was conducted through a cycle of action research consisting of four stages: planning, action, observation, and reflection. The research involved teachers and eighth-grade students at a junior high school. The results of the study showed a significant increase in student engagement in learning, indicated by the observation scores of students in the first cycle (70%), which increased in the second cycle (85%). Wordwall helped students understand and internalize Islamic religious concepts and values better, especially through activities based on simulation and visualization. The implication of this research is the need for integrating Wordwall media into the PAI curriculum to create more engaging and effective learning for teachers, schools, and students.